STUDY OF WAYS TO RESTORE THE BIOPRODUCTIVITY OF PASTURES - Nasiyev, B. N.; Zhanatalapov, N. Zh.; Bekkaliyev, A. K.; Khiyasov, M. G.; Popov, D. V. (Ғылым, зерттеулер, білім беру: даму үрдістері: ХХІІІ халықаралық ғылыми-практ. конф. материалдары=Science, research, education: development trends: The materials of the XXIII international scientific and practical conf. =Наука, исследования, образование: тенденции развития: мат. ХХІІІ междунар. науч.-практ. конф. (Уральск, 14 апреля 2023 г.) / ЗКАТУ им. Жангир хана // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 2 (71) : прил. к журналу № 2, 2023)
Currently, the area of downed and overgrown pastures with non-edible and poisonous plants is growing in the West Kazakhstan region. The area of degraded lands in places of watering and recreation of animals is especially large. The range of pastures around the villages expanded to 7-9 km . In general, the dynamics of these processes currently allows us to predict with a high degree of confidence the expansion of pasture degradation to 50% of their area. The unfavorable condition of pastures is explained not only by the natural features of the region. To an even greater extent, this is the result of anthropogenic impact. So, in recent years, in the pursuit of profit, agricultural formations, especially farms, without taking into account the conditions of pasture lands, have begun to intensively increase the number of agricultural animals. As a result, this led to a significant increase in pasture load, reduced the yield and feed intensity of pasture lands, intensified the processes of desertification in vast territories. The condition of sandy pastures, which used to be mainly used as winter pastures, is especially unfavorable, today they are also used in other seasons. In order to prevent negative anthropogenic impact on pastures in modern agricultural production, the adaptive strategy for further increasing the production of food and agricultural raw materials should be based on the principles of rational nature management, the system of which includes a number of measures, of which the most important are: seasonality of grazing pastures, taking into account the state of vegetation cover, its yield; establishment of the optimal load of livestock per unit area.В настоящее время в Западно-Казахстанской области растет площадь сбитых и заросших непоедаемыми и ядовитыми растениями пастбищ. Особенно велика площадь деградированных угодий в местах водопоя и отдыха животных. Сбой пастбищ вокруг аулов расширялся до 7-9 км. В целом динамика этих процессов в настоящее время позволяет с высокой долей уверенности прогнозировать расширение деградации пастбищ до 50% их площади. Неблагоприятное состояние пастбищ объясняется не только природными особенностями региона. Еще в большей мере это результат антропогенного воздействия. Так, в течение последних лет в погоне за прибылью сельскохозяйственные формирования, особенно фермерские хозяйства без учета состояний пастбищных угодий стали интенсивно нарашивать поголовье с.х. животных. В итоге это привело к существенному повышению пастбищной нагрузки, снизило урожайность и кормоемкость пастбищных угодий, усилило процессы опустынивания на огромных территориях. Особенно неблагополучно состояние песчаных пастбищ, используемые раньше, главным образом, в качестве зимних, сегодня они используются и в другие сезоны.В целях предотвращения отрицательного антропогенного воздействия на пастбища в современном с.х. производстве в основу адаптивной стратегии дальнейшего нара¬щивания производства продуктов питания и сельскохозяйственного сырья должны быть положены принципы рационального природопользования, в систему которого входит целый ряд мероприятий, из которых наиболее важными являются: сезонность стравливания пастбищ с учетом состояния растительного покрова, его урожайности; установление оптимальной нагрузки скота на единицу площади
Keywords: научный журнал; конференции; отечественное издание; пастбища; качество корма; bioproductivity; rational use; Tumat